Peran Pemerintah Desa Dalam Mewujudkan Desa Mandiri Di Desa Sungai Pinang Kecamatan Tambang Kabupaten Kampar - Nuraini Syafitri Nuraini Syafitri; Abdul Sadad (UIR Press, 2022)
This research was conducted with the aim of knowing how the role of the Sungai Pinang village government in the mining district of Kampar Regency in realizing a developed and independent village and the factors that influence it. This type of research is a descriptive research with a qualitative approach. Data was collected using field observations, interviews, and documentation of both primary and secondary data. The results of this study indicate that the role of the village government in realizing an advanced and independent village in Sungai Pinang Mining District, Kampar Regency is not yet optimal where the village government is still not able to utilize existing natural resources and limited funds and the community is still passive in participating.